PEMILIHAN MEDIA DALAM PEMBELAJARAN KREATIF BAGI SISWA SEKOLAH DASAR - Hari Purwanto (Lembaga Pendidikan dan Pelatihan Sindotech, 2023)
Interest in learning is an important attraction in increasing student learning motivation, the use of unique learning media such as the Neorpad application is expected to encourage students to study hard. The study aims to determine the feasibility of media in learning, targeting grade IIIA and IIIB elementary school students at SDN Ketegan 1 Taman Sidoarjo with a total of 40 students. This research uses qualitative type of Research and Development with lee and owens model development model with 5 stages. Feasibility tests were obtained by media experts by 88% while learning design experts were 86%. In the small group test, it was 82.86% while the large group test was 84.22%. Based on testing, it was found that the use of the Neorpad application can provide learning motivation for elementary school students.